1995
DOI: 10.1097/00005392-199503001-00018
|View full text |Cite
|
Sign up to set email alerts
|

Original Articles

Abstract: From November 1984 to April 1989, 122 patients with clinical T2-4a Nx-2 M0 transitional cell carcinoma of the bladder were entered in a prospective randomized trial to compare survival between a control group of 60 patients treated only with radical cystectomy (arm A) and a group of 62 patients treated with 3 cycles of 100 mg./m.2 neoadjuvant cisplatin before radical cystectomy (arm B). Secondary objectives of the trial were comparison of the disease-free interval and time to death, significance of response of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Although cisplatin is the most effective single agent for the treatment of muscle-invasive bladder cancer, up to 50% of patients are ineligible for cisplatin-containing chemotherapy [15]. Furthermore, Martinez-Pineiro et al  observed that bladder cancer progressed in 9.7% of patients during chemotherapy [16]. …”
Section: Current Chemotherapy For Bladder Cancermentioning
confidence: 99%
“…Although cisplatin is the most effective single agent for the treatment of muscle-invasive bladder cancer, up to 50% of patients are ineligible for cisplatin-containing chemotherapy [15]. Furthermore, Martinez-Pineiro et al  observed that bladder cancer progressed in 9.7% of patients during chemotherapy [16]. …”
Section: Current Chemotherapy For Bladder Cancermentioning
confidence: 99%